2015
DOI: 10.3354/meps11034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the gut microbiomes of 12 bony fish and 3 shark species

Abstract: We used massively parallel sequencing (pyrosequencing) of 16S rRNA genes to compare the composition of microbial communities in the guts of 12 bony fish and 3 shark species. The species analyzed encompass herbivores and carnivores with varied digestive physiologies, are classified as pelagic and demersal species, and reside in estuarine to marine environments. We also compared the gut microbial assemblages of wild and cultured Fundulus heteroclitus and of juvenile and adult Lagodon rhomboides. A total of 1 214… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
256
6
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(294 citation statements)
references
References 57 publications
29
256
6
3
Order By: Relevance
“…As intestinal microbiota of fish play a key role in health, understanding the interactions between fish and gut microbiota is an important research field for fish health and aquaculture (van Kessel et al, 2011). Initial studies have shown that fish harbour a diverse microbiota, dependent on host species (Sullam et al, 2012, Li et al, 2014, Givens et al, 2015), life cycle stage (Giatsis et al, 2014, Ingerslev et al, 2014a, Zarkasi et al, 2014, Zarkasi et al, 2016) and diet (Navarrete et al, 2013, Wong et al, 2013, Ingerslev et al, 2014b). Fish present a unique case among vertebrates with microorganisms from environmental sources potentially having a much higher influence on bacterial composition and health status due to constant contact with water (Austin, 2006, Ringø et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As intestinal microbiota of fish play a key role in health, understanding the interactions between fish and gut microbiota is an important research field for fish health and aquaculture (van Kessel et al, 2011). Initial studies have shown that fish harbour a diverse microbiota, dependent on host species (Sullam et al, 2012, Li et al, 2014, Givens et al, 2015), life cycle stage (Giatsis et al, 2014, Ingerslev et al, 2014a, Zarkasi et al, 2014, Zarkasi et al, 2016) and diet (Navarrete et al, 2013, Wong et al, 2013, Ingerslev et al, 2014b). Fish present a unique case among vertebrates with microorganisms from environmental sources potentially having a much higher influence on bacterial composition and health status due to constant contact with water (Austin, 2006, Ringø et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The fish intestine can harbour 10 7 to 10 11  bacteria/g intestinal content, with aerobes and facultative anaerobes being more abundant than obligate anaerobes, and can be split between the autochthonous species that are attached to the intestinal mucosa and the allochthonous that do not attach either due to lack of ability or outcompetition by mucous attached bacteria (Nayak, 2010, Navarrete et al, 2012, Llewellyn et al, 2014, Givens et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The microbiomes of diverse marine animals are currently under study, from simplistic organisms including sponges (e.g., Webster et al, 2010) and ctenophores (Daniels and Breitbart, 2012) to more complex organisms such as sea squirts (Blasiak et al, 2014) and sharks (Givens et al, 2015). Below I present some of the current study systems that represent a diverse cross-section of marine animal phyla, and trends of research in these systems including focus on symbiosis and dysbiosis.…”
Section: Overview Of Diverse and Emerging Animal-microbiome Study Sysmentioning
confidence: 99%
“…BOX FIGURE 1 | Depiction of a coral reef and associated microbiomes with organismal hosts [i.e., invertebrates Tianero et al, 2014;Hakim et al, 2016), seagrass (Ettinger et al, 2017;Fahimipour et al, 2017), fish (Ghanbari et al, 2015;Givens et al, 2015;Parris et al, 2016), corals (Barott et al, 2011;Blackall et al, 2015;Hester et al, 2016), macroalgae (Barott et al, 2011;Burke et al, 2011;Egan et al, 2013;Brodie et al, 2016), sponges Blackall et al, 2015), turf algae (Hester et al, 2016)] and environmental parameters [i.e., reef water (McCliment et al, 2012), sediment (Ettinger et al, 2017)]. The size of the bubble indicates a more species rich microbiome (based on OTUs).…”
Section: Overview Of the Beneficial Roles That Bacteria Play In Coralsmentioning
confidence: 99%